Diagnosis and ECMO Treatment of a Critically Ill Patient With Disseminated Mycobacterium tuberculosis: A Case Report - Shang, Xiuling; Zhang, Hongxuan; Chen, Sheng; Wang, Chen; Lin, Meifu; Yu, Rongguo (Frontiers in Public Health, 2022)
BACKGROUND: Mycobacterium tuberculosis infection remains a public health concern worldwide. The diagnosis and treatment of disseminated mycobacterium tuberculosis is very difficult, so we shared our experiences and lessons learned in this case report. CASE PRESENTATION: A 36-year-old female with a history of epilepsy presented to our hospital with fever, upper abdominal pain, muscle soreness in limbs for seven days, and shortness of breath for four days. On admission, she presented with acute respiratory distress syndrome (ARDS) and liver dysfunction. Due to the critical nature of her clinical presentation, the patient was admitted directly to the Intensive Care Unit (ICU), received mechanical ventilation in prone position and VV-ECMO treatment. Her condition improved gradually, and the ECMO was removed after seven days and she was weaned off the ventilator after eight days. However, her fever recurred and she underwent PET-CT examination, liver contrast ultrasound, acid-fast staining and second-generation sequencing of cerebrospinal fluid, which confirmed Mycobacterium tuberculosis infection. CONCLUSION: This case report briefly described the treatment and diagnosis of a critically ill patient with intra and extra-pulmonary tuberculosis infection. Timely and appropriate treatment is crucial to save lives, but the timing of ECMO treatment needs to be carefully considered for patients with ARDS caused by tuberculosis, because ECMO may cause hematogenous dissemination of tuberculosis.